2006
DOI: 10.1021/ja064868m
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Rhodium-Catalyzed [2+2+2] Cycloaddition of Alkenyl Isocyanates and Terminal Alkynes:  Application to the Total Synthesis of (+)-Lasubine II

Abstract: The use of TADDOL-based phosphoramidite ligands on rhodium allows for the incorporation of terminal alkynes in the [2+2+2] cycloaddition with alkenyl isocyanates. Terminal aliphatic alkynes provide bicyclic lactams, while the use of aryl alkynes provides complementary access to vinylogous amides. Product selectivity seems to be governed by a combination of electronics and sterics, with smaller and/or more electron-deficient substituents favoring lactam formation. The use of homologous alkenyl isocyanates leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(45 citation statements)
references
References 15 publications
3
42
0
Order By: Relevance
“…4 We have observed that the phosphoramidite oxidizes under acidic conditions and purification via column chromatography can result in partially oxidized ligand. Recrystallization avoids use of acidic silica for purification and makes the overall isolation of the ligand easier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 We have observed that the phosphoramidite oxidizes under acidic conditions and purification via column chromatography can result in partially oxidized ligand. Recrystallization avoids use of acidic silica for purification and makes the overall isolation of the ligand easier.…”
Section: Discussionmentioning
confidence: 99%
“…We have traditionally synthesized alkenyl isocyanates in one of two ways: conversion of the acyl azide to the isocyanate under reduced pressure 4 and column chromatography of the acyl azide followed by neat conversion. 5 These methods work well for small scale, but on larger scale, these approaches can potentially be dangerous if proper precautions are not observed.…”
Section: Discussionmentioning
confidence: 99%
“…170 Due to the CO-migration associated with this enantioselective [2+2+2] annulation, the bonds targeted for formation with this process are a bit different than typically seen in [2+2+2] annulation methods. Here, the four C–C bonds highlighted in Figure 55A were those that would derive from the annulation process.…”
Section: Metallacycle-mediated Cross-coupling By [2+2+2]mentioning
confidence: 99%
“…[7,8] Over the past years, these phosphorus ligands have been successfully applied in the asymmetric hydrogenation of a range of prochiral olefins, including a-and b-dehydroamino acids and esters, [9] itaconic acid and its dimethyl ester, [9b-e] enol acetates and enol carbamates, [10] enamides, [11] acrylic acids [12] and imines. [13] Besides asymmetric hydrogenation, this class of ligands has also been successfully applied in the enantioselective copper-catalyzed conjugate addition of dialkylzinc reagents, [14] in asymmetric hydrosilylation, [15] in asymmetric hydrovinylation, [16] in asymmetric cyclopropanation, [17] in allylic substitution, [18] in the asymmetric Phauson-Khand reaction, [19] in the asymmetric Heck reaction, [20] in asymmetric cycloisomerization, [21] in asymmetric allyl alcohol isomerization, [22] in asymmetric [2 + 2 + 2] cycloaddition [23] and in asymmetric arylations using arylboronic acids. [24] …”
Section: Pharmaceuticalmentioning
confidence: 99%